2021
DOI: 10.2147/ott.s295716
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic Melanoma: A Clinicopathological Analysis of Three Cases in the Chinese Population

Abstract: Purpose: To investigate the clinicopathological characteristics and immunophenotype of desmoplastic melanoma (DM) in the Chinese population. Patients and Methods: We report three cases of DM diagnosed by the Pathology Department of Shanghai Dermatology Hospital. We describe the clinical and pathological characteristics of the three cases and examine molecular markers used in the diagnosis of DM. Finally, we summarize the current literature in the DM field. Results: Clinically, lesions in the three DM patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…13,37 These 53 studies were published from 1971 to 2021 and included 3,080 DM; they consisted of 2 single-arm prospective studies (evaluating WLE for DM 39 or WLE and adjuvant radiation for DM 40 ), 1 case control study (comparing DM with other melanoma subtypes), 41 and 50 case series (see Supplemental Digital Content , Table S2, http://links.lww.com/DSS/B209, for studies). 7,11,13–25,30,37,39–74 The studies had a high risk of bias per the ROBINS-I assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…13,37 These 53 studies were published from 1971 to 2021 and included 3,080 DM; they consisted of 2 single-arm prospective studies (evaluating WLE for DM 39 or WLE and adjuvant radiation for DM 40 ), 1 case control study (comparing DM with other melanoma subtypes), 41 and 50 case series (see Supplemental Digital Content , Table S2, http://links.lww.com/DSS/B209, for studies). 7,11,13–25,30,37,39–74 The studies had a high risk of bias per the ROBINS-I assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported LRR associated with or without adjuvant radiation therapy. 13,19,20,25,40,43,45,48,53,55,56,64,68 11 studies included tumors treated with or without adjuvant radiation 13,19,20,25,40,45,48,55,56,64,68 and 2 studies exclusively included patients treated with adjuvant radiation. 43,53 Data from all 13 studies were analyzed to calculate and compare summary estimates of LRR by use of adjuvant radiation.…”
Section: Local Recurrence Rate For Wle-treated Dm Associated With or ...mentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 2 Initially described by Conlev et al, 3 as a superficial melanotic lesion with the histology of locally invasive fibrous tumors, DM has slowly increased in incidence. 4 Epidemiologically, risk remains highest in chronically sun-exposed individuals, with a male to female ratio of 2:1, and in older individuals, with a mean age of onset of 66 years. 1 …”
Section: Introductionmentioning
confidence: 99%